Intracellular survival of Streptococcus pneumoniae in human alveolar macrophages is augmented with HIV infection - Nyazika, Tinashe K.; Sibale, Lusako; Phiri, Joseph; De Ste Croix, Megan; Jasiunaite, Zydrune; Mkandawire, Christopher; Malamba, Rose; Kankwatira, Anstead; Manduwa, Miriam; Ferreira, Daniela M.; Nyirenda, Tonney S.; Oggioni, Marco R.; et al. (Frontiers in Immunology, 2022)
People Living with HIV (PLHIV) are at an increased risk of pneumococcal pneumonia than HIV-uninfected adults, but the reasons for this are still not well understood. We investigated whether alveolar macrophages (AM) mediated control of pneumococcal infection is impaired in PLHIV compared to HIV-uninfected adults. We assessed anti-bactericidal activity against Streptococcus pneumoniae of primary human AM obtained from PLHIV and HIV-uninfected adults. We found that pneumococcus survived intracellularly in AMs at least 24 hours post ex vivo infection, and this was more frequent in PLHIV than HIV-uninfected adults. Corroborating these findings, in vivo evidence showed that PLHIV had a higher propensity for harboring S. pneumoniae within their AMs than HIV-uninfected adults. Moreover, bacterial intracellular survival in AMs was associated with extracellular propagation of pneumococcal infection. Our data suggest that failure of AMs to eliminate S. pneumoniae intracellularly could contribute to the increased risk of pneumococcal pneumonia in PLHIV.